SUSTAINING ENTREPRENEURIAL INTENTION WITH ENTREPRENEURIAL LEARNING, ENTREPRENEURIAL KNOWLEDGE, HUMAN CAPITAL - Ida Ketut Kusumawijaya; Partiwi Dwi Astuti (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2024)
This study examines the effect of entrepreneurial learning on entrepreneurial intention through entrepreneurial knowledge and human capital during the COVID-19 pandemic. The population of this study were 7,246 students majoring in business from Bali's universities. The sample size was 379 with the Slovin method. The link to the online survey was sent to respondents via email. Two hundred seventy-nine questionnaires were returned and confirmed valid, with a usable response rate of 73.61%. The results were analyzed using WarpPLS 7.0. The study resulted that entrepreneurial learning influenced knowledge, human capital, and intention. Entrepreneurial knowledge did not affect entrepreneurial intention, and human capital affected entrepreneurial intention. This study also found that entrepreneurial knowledge had almost no mediating effect between entrepreneurial learning and entrepreneurial intention, and human capital succeeded in being a partial mediator on the influence of entrepreneurial learning on entrepreneurial intention. Moreover, this study contributes to the understanding and is useful for scholars, academics, and practitioners in the field of entrepreneurship to create a broader view of the relationship between entrepreneurial learning, entrepreneurial knowledge, human capital, and entrepreneurial intention and mediation mechanism that occurs in the model for the conceptual generalization and entrepreneurial practices purposes.